Associations of Physical Activity and Sedentary Behaviour with Vision-Threatening Diabetic Retinopathy in Indonesian Population with Type 2 Diabetes Mellitus: Jogjakarta Eye Diabetic Study in the Community (JOGED.COM). (4th March 2018) - Dharmastuti, D.P; Agni, A.N; Widyaputri, F; Pawiroranu, S; Sofro, Z.M; Wardhana, F.S; Haryanto, S; Widayanti, T.W; Kotha, S; Gupta, P; Sasongko, M.B
ABSTRACT: Purpose : To investigate the association of physical activity (PA) and sedentary behaviour with diabetic retinopathy (DR) in type 2 diabetes adults. Methods : A community-based cross-sectional study of adults with type 2 diabetes. DR was assessed from disc- and macula-centred fundus photograph, and categorised into mild, moderate non-proliferative DR (NPDR), and Vision-Threatening DR (VTDR). Worse eye was used to determine the person's DR severity. PA was assessed using WHO Global Physical Activity Questionnaire (GPAQ). All of the PA components, including daily sitting time, walking distance, sleeping duration, and exercise were converted based on the physical activity ratio and then calculated to obtain the mean physical activity level (PAL). The mean PAL was then classified into sedentary, moderate, and vigorous lifestyle. Results : There were 1116 participants, 43.1% with any DR and 26.3% VTDR. The prevalence of DR/VTDR in sedentary, moderate, and vigorous physical activity group was 41.9%/22.7%, 39.2%/23.9%, and 32.7%/20.4% respectively. A longer duration of daily sedentary lifestyle (>3 hours) was significantly associated with presence of DR (OR 1.66; 95% CI 1.17–2.35; p < 0.01) and VTDR (OR 1.74; 1.16–2.62; p < 0.01). These associations remained significant after adjusting for age, gender, duration of diabetes, systolic blood pressure and physical activity. There was no significant association between sleeping duration, walking distance, and vigorous activity and DR. Conclusions : In this study, prolonged daily sedentary activity was strongly associated with VTDR. This finding suggests that public health campaign for reducing daily sedentary activities in individuals with type 2 diabetes may offer benefit to reduce the burden of DR and VTDR.